Brain target occupancy of LY3372689, an inhibitor of the O‐GlcNAcase (OGA) enzyme, following administration of single and multiple doses to healthy volunteers - Kielbasa, William; Shcherbinin, Sergey; Goldsmith, Paul; Phipps, Krista M; Biglan, Kevin; Mancini, Michele; Russell, David; Constantinescu, Cristian; Gunn, Roger N; Nuthall, Hugh Norman; Mergott, Dustin J.; Lowe, Stephen L; et al. (Alzheimer's & dementia, 2021)
Background LY3372689, an O‐GlcNAcase (OGA) enzyme inhibitor, is being developed as a potential treatment of tauopathies, including Alzheimer’s disease. OGA inhibition is proposed to delay the progression of tau‐related diseases by slowing the accumulation of hyper‐phosphorylated, insoluble tau filaments. We report on single dose (SD) and multiple dose (MD) clinical studies testing the effect of LY3372689 on brain OGA enzyme occupancy (EO). Method A positron emission tomography (PET) radioligand, 18F‐LY3316612, was used to assess brain OGA EO in healthy volunteers (HV). In the SD study [NCT03944031], 0.25, 1 and 5 mg LY3372689 were evaluated across 4 cohorts (N = 4 HV per cohort). Each HV had PET scans at baseline and two post‐dose intervals. Post‐dose scans occurred at 2 and 24 hours at 0.25, 1, and 5 mg, with additional scans for 1 mg at 30 and 54 hours. The MD study [NCT04392271] consisted of 1 cohort (N = 4 HV) given 1 mg LY3372689 once daily for 14 days. Each HV had a baseline PET scan, and PET scans at 24 hours post‐dose after the 1st and 14th administration of LY3372689. Plasma pharmacokinetics was assessed in these studies. Result In the SD study, the mean brain OGA EO at 5 mg was 98% at 2 hours and 93% at 24 hours. At 1 mg, the mean EO was 97% at 2 hours, 81% at 24 hours, 68% at 30 hours, and 30% at 54 hours. The EO at 0.25 mg was lower at 2 hours (26%) compared to 24 hours (46%). The Emax and EC50 values were estimated to be 97% and 0.1 ng/mL, respectively. In the MD study, the OGA EO at 24 hours after the 1st and 14th administration of 1 mg LY3372689 was 84%. Conclusion PET studies in healthy volunteers demonstrated that LY3372689 can achieve high brain target occupancy of the OGA enzyme. Brain OGA EO was maintained after multiple dosing, supporting the durability of target engagement for longer clinical trials. The human PET data will be used to support LY3372869 dose selection for efficacy trials in tauopathies.